Ambidextrous capacity in small and medium-sized enterprises - Felício, J. Augusto (2022)
This study examines the ambidextrous capacity—the ability to respond simultaneously to both disruptive and incremental innovation processes—of small and medium-sized enterprises (SMEs) in Portugal. The purpose is to understand the organizational ambidexterity of SMEs and its relationship to organizational performance and innovation capacity. The objectives are to evaluate the characteristics that identify ambidextrous organizations and analyze the effect of organizational ambidexterity on performance, supported by the contingency-based approach, organizational theory, behavioral theory of the firm, and organizational learning theory. After factor analysis is performed, a structural equations model is used to analyze a sample of 202 valid responses. The analysis shows that, for SMEs, disruptive innovation factors relate mainly to innovation capacity and incremental innovation factors relate to organizational performance. The confirmation of organizational ambidexterity in SMEs and the increased recognition of the importance of disruptive innovation are relevant contributions to the literature.